2019
DOI: 10.1093/jxb/erz003
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and hydrogen peroxide regulate formation of a sterol-enriched domain essential for wall labyrinth assembly in transfer cells

Abstract: Ethylene and extracellular hydrogen peroxide co-regulate formation of a sterol-enriched plasma membrane domain in trans-differentiating epidermal transfer cells that functions to co-ordinate construction of their wall labyrinth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…In the case of UWL formation (Fig. 7), our previous studies suggested that the PM-located apo H 2 O 2 signal acted by inducing a microtubule/actin-independent polarized vesicle docking system, embedded in sterol-enriched domains, located along the entire outer periclinal region of the ETC PM (Zhang et al , 2019). In contrast, the concurrent VfrbohB/PAO/Prx original wall-generated apo H 2 O 2 signal, residing in the cell wall matrix, played no role in UWL construction.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In the case of UWL formation (Fig. 7), our previous studies suggested that the PM-located apo H 2 O 2 signal acted by inducing a microtubule/actin-independent polarized vesicle docking system, embedded in sterol-enriched domains, located along the entire outer periclinal region of the ETC PM (Zhang et al , 2019). In contrast, the concurrent VfrbohB/PAO/Prx original wall-generated apo H 2 O 2 signal, residing in the cell wall matrix, played no role in UWL construction.…”
Section: Discussionmentioning
confidence: 90%
“…This was shown to be guided by an extensive transmembrane polymeric platform formed by Casparian Strip domain proteins (CASPS) (Lee et al , 2013). In contrast, for trans -differentiating ETCs, apo H 2 O 2 would appear to direct spatial organization of lipid-enriched domains in the outer periclinal region of the PM (Zhang et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is mediated by apo H 2 O 2 upregulating a cytoskeleton‐independent mechanism of docking/fusion of vesicles carrying cargoes of phytosterols while blocking their endocytosis in the outer periclinal region of the ETC plasma membrane (Fig. 4c; Zhang et al ., 2019). In line with these roles, catalytic activities of plasma membrane‐localized Prxs are evenly spread across the plasma membrane lining the outer periclinal wall during UWL formation.…”
Section: Unmasking Master Regulators and Signals Directing Wall Labyrmentioning
confidence: 99%